The use of LabVIEW programs for the production of craft alcoholic beverage - Herrera, Juan Pablo; Padilla, Victoria; Moreno, Mayerllyn (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
Sugar cane has been used as raw material for the production of craft alcoholic beverages, whose manufacturing process is part of the culture of several municipalities in the Táchira state. The production of this type of alcoholic beverage has been legal since 2007; however, most of the traditional ethanol production is generated in a clandestine manner from the fermentation of the by-products of sugar cane. The artisanal producers do not use any selection criteria of distillate or product quality control; as a result, these beverages have toxic impurities which preclude their legalization. To increase product quality it is necessary to apply the selection criteria of the distillate and to determinate the ethanol concentration taking into account the conditions under which the process is developed. Therefore, the LabVIEW programs were designed to define the collection parameters of distillate and to determinate the ethanol concentration in the solution by the density, in order to remove the toxic products and facilitate the possibility of the legalization.